ANALISIS PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES) HARAPAN OESENA DI DESA OESENA KECAMATAN AMARASI KABUPATEN KUPANG - Ade Onny Siagian (Jurnal Riset Entrepreneurship, 2021)
This research aims to analyze the economic potential in Oesena village, analyze the management progress of Oesena village, analyze the strength, the weakness, the opportunity, and the threat in developing the BUMDes of Oesena village. This research was the type of case study research that used descriptive qualitative approach. This research used the way of analysing the strategy and the meaning qualitatively. In deciding the informants for this research, the purposive sampling technique where the decision of the informants was done consciously according to some criteria and the informants were people who could give the informations about BUMDes in Oesena village to the researcher. There were two techniques for analysing the data such as the technique of data analysis and the technique of SWOT analysis. The research results showed that the development of BUMDes in Oesena Village was still unstable. It could be seen from lack of support for the economic potentials in this village, lack of participation or the follow-up from the BUMDes manager and also the villagers;The progress level of this village was still low and there was no significant increase; the strengths could be seen from the potentials of natural resources, weavings, and the villagers’ soft skills, the weakness could be seen from the limited potential of human resources, the lack of understanding and initiative of the villagers, the opportunities could be seen from the utilization of BUMDes as the economy source in helping the villagers to keep their needs that also could increase the PAD, the last next one was the threat that could be seen from the low rating and also from the lack of villager’s cooperation, there was also no strategy from the BUMDes managers. But the business unit, the saving and loan, the rent and tourism were known as the solutions for all the problems and as the solutions in keeping the villgers’ needs at Oesena village in Amarasi sub-district of Kupang district.